Breaking Legal Inequality Traps : New Approaches to Building Justice Systems for the Poor in Developing Countries /: New Approaches to Building Justice Systems for the Poor in Developing Countries. (December 2007) - Sage, Caroline Mary; Woolcock, Michael J. V, 1964-
No abstract available